Besov-type spaces for the κ-Hankel wavelet transform on the real line - Pathak Ashish (De Gruyter, 2021)
In this paper, we shall introduce functions spaces as subspaces of Lpκ (ℝ) that we call Besov-κ-Hankel spaces and extend the concept of κ-Hankel wavelet transform in Lpκ(ℝ) space. Subsequently we will characterize the Besov-κ-Hankel space by using κ-Hankel wavelet coefficients.